2011
DOI: 10.1007/s00330-011-2222-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and complication rates of percutaneous ablative techniques for the treatment of liver tumors: a systematic review

Abstract: Percutaneous RFA, PEI and MWA can be considered safe techniques for the treatment of liver tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 63 publications
10
98
0
2
Order By: Relevance
“…6,7 However, several other studies reported that RFA rarely may induce major complications and death. [3][4][5] Major complications were defined as those that delayed hospital discharge, threatened the patient's life, or led to substantial morbidity and disability. 8 In a multicenter study, reported rates of mortality and major complications of RFA for HCC were about 0.15% and 4.0%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,7 However, several other studies reported that RFA rarely may induce major complications and death. [3][4][5] Major complications were defined as those that delayed hospital discharge, threatened the patient's life, or led to substantial morbidity and disability. 8 In a multicenter study, reported rates of mortality and major complications of RFA for HCC were about 0.15% and 4.0%.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a multicenter study, reported rates of mortality and major complications of RFA for HCC were about 0.15% and 4.0%. 3 Complications arising from RFA can be divided into two general categories: those related to imaging guided electrode placement, and those related to thermal transmission. 9 Even though the most common major complication due to thermal transmission was hepatic abscess in the multicenter study, 3 RFA may cause thermal injury to extrahepatic structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strictures are best imaged with MRCP, but CT or ultrasound can also show the segmental biliary dilatation resulting from strictures. Bile duct injury that may lead to biliary leaks, bilomas, and fi stulas is exceedingly rare, occurring in less than 0.1 % of cases (Curley et al 2004 ;Bertot et al 2011 ). Bilomas can form along S.Z.…”
Section: Abbreviationsmentioning
confidence: 99%